2020
DOI: 10.3390/ijms21114174
|View full text |Cite
|
Sign up to set email alerts
|

Serum Biomarkers of Cardiovascular Remodelling Reflect Extra-Valvular Cardiac Damage in Patients with Severe Aortic Stenosis

Abstract: In patients with aortic stenosis (AS), a novel staging classification of extra-valvular left and right heart damage with prognostic relevance was introduced in 2017. The aim of the study was to evaluate the biomarkers of cardiovascular tissue remodelling in relation to this novel staging classification. Patients were categorized according to the novel staging classification into stages 0 to 4. The levels of matrix metalloproteinase 9 (MMP-9), tissue inhibitor of metalloproteinases 1 (TIMP-1), B and C domain co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
(80 reference statements)
1
12
0
Order By: Relevance
“…When comparing ED-A + and ED-B + Fn serum levels in PH patients and healthy controls, we observed significantly increased levels for ED-A + but not for ED-B + Fn qualifying ED-A + Fn as a promising biomarker in PH. This goes in line with recent findings of our group showing a strong re-expression of the molecule in human tissue and serum samples from patients suffering from, e.g., coronary artery disease, aortic stenosis, heart failure of different aetiology or rejection after heart transplantation [26][27][28]30,33,36]. Moreover, we could report similar findings in several preclinical models of cardiac allograft vasculopathy or PH, respectively [29,31,32,37].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When comparing ED-A + and ED-B + Fn serum levels in PH patients and healthy controls, we observed significantly increased levels for ED-A + but not for ED-B + Fn qualifying ED-A + Fn as a promising biomarker in PH. This goes in line with recent findings of our group showing a strong re-expression of the molecule in human tissue and serum samples from patients suffering from, e.g., coronary artery disease, aortic stenosis, heart failure of different aetiology or rejection after heart transplantation [26][27][28]30,33,36]. Moreover, we could report similar findings in several preclinical models of cardiac allograft vasculopathy or PH, respectively [29,31,32,37].…”
Section: Discussionsupporting
confidence: 92%
“…In a very recent study, including elderly patients suffering from severe symptomatic aortic stenosis, our group investigated a panel of biomarkers with respect to their association to the novel staging classification of extra-valvular cardiac damage [38]. Interestingly, ED-A + Fn was significantly increased in aortic stenosis patients additionally exhibiting PH with or without consecutive right heart failure, compared to patients in which the disease was restricted to the left side of the heart [36]. In contrast to ED-A + Fn, a variety of studies investigating ED-B + Fn revealed that its re-expression is strongly linked to cancer development and tumour-associated angiogenesis and not to non-neoplastic chronic inflammatory diseases [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of various studies investigating the value of novel biomarkers of cardiovascular remodeling for improving the diagnosis or estimating the prognosis of AS patients [22,25,26,37], to our best knowledge, none of these markers has ever been implemented into a long-term mortality risk prediction model after TAVI. Thus, the JMS presented here, might fill this gap by integrating circulating levels of TIMP-1, which is a well-known biomarker of cardiovascular ECM accumulation and fibrosis [22,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…For the following biomarkers, commercially available assays were used according to the instructions of the manufacturer: matrix metalloproteinase 9 (MMP-9; assay: Human MMP-9 Immunoassay, R&D Systems GmbH, Wiesbaden, Germany), tissue inhibitor of metalloproteinase 1 (TIMP-1, assay: Human TIMP-1 Immunoassay, R&D Systems GmbH, Wiesbaden, Germany), B domain containing tenascin-C (B + Tn-C, assay: Tenascin-B Large (FNIII-B) ELISA, IBL International GmbH, Hamburg, Germany), endothelin 1 (ET-1, assay: Endothelin-1 Immunoassay, R&D Systems GmbH, Wiesbaden, Germany) and neutrophil gelatinase-associated lipocalin (NGAL, assay: Human Lipocalin-2/NGAL Immunoassay, R&D Systems, Wiesbaden, Germany). For the serum quantification of extra domain A containing fibronectin (ED-A + Fn) and extra domain B containing fibronectin and (ED-B + Fn), we applied protocols, which were recently established and validated in our group [22,32,33] because commercial ELISA assays are not available at present.…”
Section: Blood Sample Acquisition and Measurement Of Routine Laborato...mentioning
confidence: 99%
See 1 more Smart Citation